(untitled) (The Pakistan Development Review, 2011)
This study empirically verifies the existence of significant relationship between inflation and trade openness for Pakistan using annual time-series data for the period of 1976 to 2010. The basic objective of this study is to examine the Romer‘s hypothesis for Pakistan with real agriculture value added, real exchange rate, real gross domestic product, financial market openness, money and quasi money and used trade openness, import openness and export openness ratios separately as explanatory variables with inflation rate as dependent variables. For this purpose, we have used multivariate Johansen (1998) and Johansen and Juselius (1990) Maximum Likelihood Cointegration Approach and a Vector Error Correction Model (VECM) and the expected empirical findings shows that there is a significant positive long-run relationship between inflation and trade openness, which rejects the existence of Romer‘s hypothesis for Pakistan. JEL classification: B26, E31, P24, P44 Keywords: Trade Openness, Inflation, Unit Root Testing, Multivariate Cointegration Approach, Vector Error Correction Model, Pakistan